2011
DOI: 10.1016/j.ecoleng.2010.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of high-strength wastewater in tropical constructed wetlands planted with Sesbania sesban: Horizontal subsurface flow versus vertical downflow

Abstract: a b s t r a c tTreatment of various types of wastewaters is an urgent problem in densely populated areas of many tropical countries. We studied the potential of using Sesbania sesban, an N 2 -fixing shrub, in constructed wetland systems for the treatment of high-strength wastewater. A replicated horizontal subsurface flow system and a saturated vertical downflow system was established with planted and unplanted beds to assess the effects of system design and presence of plants on treatment performance. The sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…Pan et al [13] also observed that, when HLR is increased, the removal efficiencies of NH 4 + -N and TN decreased, which is similar to what was found by others authors [43,44]. Although lower HLR generally resulted in better removal efficiencies of N compounds, RE did not significantly (p > 0.05) correlate with HLR and the linear relationships between HLR as independent variable and removal percentage were rather weak for all nitrogen compounds and for all monitoring periods, with coefficient of determination (R 2 ) always less than 0.4356.…”
Section: Nitrogen Removalsupporting
confidence: 76%
See 1 more Smart Citation
“…Pan et al [13] also observed that, when HLR is increased, the removal efficiencies of NH 4 + -N and TN decreased, which is similar to what was found by others authors [43,44]. Although lower HLR generally resulted in better removal efficiencies of N compounds, RE did not significantly (p > 0.05) correlate with HLR and the linear relationships between HLR as independent variable and removal percentage were rather weak for all nitrogen compounds and for all monitoring periods, with coefficient of determination (R 2 ) always less than 0.4356.…”
Section: Nitrogen Removalsupporting
confidence: 76%
“…The negative average removal in NH 4 + -N in autumn-winter may also be related to high flushing due to the high flow rate of water through the wetland bed during the rainy months. Several authors reported that increase in N loads within certain limits tends to contribute to grater removal rates in HSSF-CWs [16,18,43,46]. The results obtained at the present study have shown that the concentrations of TN and NH 4 + -N in the effluent tend to significantly (p < 0.05) decrease with increasing respective incoming mass load rates, although the linear relationship between the two variables for the whole period (12 August-13 June) is moderate, as shown by the values found for the coefficient of determination (TN: R 2 = 0.3738; NH 4 + -N: R 2 = 0.3521).…”
Section: Nitrogen Removalmentioning
confidence: 99%
“…[3,5] However, anaerobic decomposition might account for a considerable proportion in the IVCWs, especially at high COD LR due to the low DO levels in the wetland beds. [18,19] COD mass removal rate of the IVCWs increased with the increasing LRs, which was consistent with the results obtained in other CWs, [20][21][22][23][24] and was probably due to the enhanced microbial production and metabolism under higher LR. [20] Nevertheless, a tendency of leveling off for mass removal rate at high LR was observed by Dan et al, [23] suggesting that the organics removal capacity of CW was not infinite.…”
Section: Cod Removal and The Influences Of Crucial Factorssupporting
confidence: 80%
“…In addition, the k values of COD removal in the IVCWs were in the high range of some references, [18,23,24] and higher than some others. [5,10,21] Very low effluent COD concentration (7.2 mg L…”
Section: Cod Removal and The Influences Of Crucial Factorsmentioning
confidence: 99%
See 1 more Smart Citation